Maulud Janjanen (MJ): A Tradition of Muslim Family Education in Temanggung - Muhammad shodiq Mubasyir; Muhammad Syakur; Joni; Muh. Baehaqi; Sumarjoko; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2024)
The Maulud Janjanen tradition represents a form of religious cultural expression embedded in the rural Muslim communities of Temanggung Regency. This study aims to examine the contribution of Maulud Janjanen (MJ) to the development of family character and the preservation of intangible cultural heritage within the framework of Islamic family law (fiqh al-usrah). Utilizing a qualitative approach and case study method, data were collected through interviews, participatory observation, and documentation. The findings reveal that this tradition functions as a medium for instilling spiritual and social values such as responsibility, exemplary conduct, and communal cooperation. The involvement of multiple generations establishes it as a natural mechanism for transmitting values and cultural identity. Furthermore, this practice aligns with the Islamic legal principle of ‘urf ṣaḥīḥ, where local customs are recognized as sources of law as long as they do not contradict the Sharia. This tradition remains relevant as a strategy for character education and cultural preservation amid the challenges of modernization.